2020
DOI: 10.3390/genes11030334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transgenesis on mRNA and miRNA Profiles in Cucumber Fruits Expressing Thaumatin II

Abstract: Transgenic plants are commonly used in breeding programs because of the various features that can be introduced. However, unintended effects caused by genetic transformation are still a topic of concern. This makes research on the nutritional safety of transgenic crop plants extremely interesting. Cucumber (Cucumis sativus L.) is a crop that is grown worldwide. The aim of this study was to identify and characterize differentially expressed genes and regulatory miRNAs in transgenic cucumber fruits that contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Overexpression of PdNF-YB21 increased the drought resistance of transgenic poplars by positively regulating root growth and enlarging xylem vessels [ 30 ]. Recently, some studies have demonstrated that miRNA responded to abiotic stresses by regulating the expression of their target gene NF-Y [ 31 ]. The overexpression of soybean miR169c in transgenic Arabidopsis conferred increased drought stress sensitivity via inhibiting the expression of its target AtNF - YA gene [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of PdNF-YB21 increased the drought resistance of transgenic poplars by positively regulating root growth and enlarging xylem vessels [ 30 ]. Recently, some studies have demonstrated that miRNA responded to abiotic stresses by regulating the expression of their target gene NF-Y [ 31 ]. The overexpression of soybean miR169c in transgenic Arabidopsis conferred increased drought stress sensitivity via inhibiting the expression of its target AtNF - YA gene [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the expression level of the thaumatin II gene in cucumber transgenic lines showed that transgene expression occurs in all three thaumatin lines, but the level of expression varies (Pawełkowicz et al 2020 ). The lowest expression level was obtained for 225 line, despite it having a double copy of T-DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RNA-seq and miRNA-seq analyses in the fruits of three transgenic lines (212, 224, and 225), it was concluded that transformation of the cucumber genome with thaumatin II and expression of the transgene had minimal impact on gene expression and epigenetic regulation by miRNA in the cucumber fruits (Pawełkowicz et al 2020 ). The next important step was a comparative genome analysis, which aimed to check if and how transgene insertion affects gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we also examined three independent transgenic cucumber lines (Pawełkowicz et al 2020) that were derived from the same B10 line and, after transformation, were regenerated in in vitro cultures. The changes in gene expression between transgenic lines compared with the control line (plants were grown in the same field experiment as the somaclones) were as follows: three, six, and 38 DEGs in the respective analyzed transgenic lines (Pawełkowicz et al 2020). The number of DEGs detected in the somaclonal lines was significantly higher than those observed among the transgenic lines.…”
Section: Influence Of Genome Changes On the Transcriptome Of Somaclonesmentioning
confidence: 99%